2020
DOI: 10.1515/gps-2020-0027
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic performance of the biosynthesized AgNps from Bistorta amplexicaule: antifungal, bactericidal, and reduction of carcinogenic 4-nitrophenol

Abstract: AbstractThis study was focused to synthesize silver nanoparticles (AgNps) from the aqueous extract of Bistorta amplexicaule and to evaluate their antimicrobial, antifungal, and 4-nitrophenol (4-NP) degradation potential. The AgNps from B. amplexicaule were characterized by field emission scanning electron microscopy, energy dispersive X-ray spectrometry, X-ray diffraction, and X-ray photoelectron spectroscopy studies. The bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Core-level analysis of the XPS survey indicated two prominent peaks for Ag(3d) electron binding energy: 373.68 eV for Ag0 3d 3/2 and 367.89 eV for Ag0 3d 5/2 , with a spin−orbit separation of about 5.79 eV (Figure 2c). These Ag peaks observed in the XPS analysis closely matched those reported in the literature 77 and confirmed the absence of Ag ions, indicating the presence of CHPs@AgNPs in a zero oxidation state. The core-level analysis of the XPS spectra showed a single peak at 531.3 eV for O(1s), which corresponds to the oxygen atom of the carbonyl groups (C�O) (Figure 2d).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Core-level analysis of the XPS survey indicated two prominent peaks for Ag(3d) electron binding energy: 373.68 eV for Ag0 3d 3/2 and 367.89 eV for Ag0 3d 5/2 , with a spin−orbit separation of about 5.79 eV (Figure 2c). These Ag peaks observed in the XPS analysis closely matched those reported in the literature 77 and confirmed the absence of Ag ions, indicating the presence of CHPs@AgNPs in a zero oxidation state. The core-level analysis of the XPS spectra showed a single peak at 531.3 eV for O(1s), which corresponds to the oxygen atom of the carbonyl groups (C�O) (Figure 2d).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It has been detected in industry wastewater and is toxic to aquatic life, humans and animals and thus has to be removed (Yang et al, 2023;Chen et al, 2017). Previous research has demonstrated greensynthesized AgNPs as a more sustainable and environmentally friendly alternative to conventional catalysts which utilize expensive chemicals and generate toxic by-products in the process (Rani et al, 2020;Shah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%